PENGARUH PENERAPAN MODEL PEMBELAJARAAN KOOPERATIF TIPE NUMBERED HEDS TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 20 SIJUNJUNG (JURNAL LEMMA, 2019)
The problem in this research about the result of students learning outcomes are still low. This research aims to determine whether students learning outcomes by applying the Numbered Heads Together (NHT) type of cooperative learning model is better than studentsmathematics learning outcomes by applying conventional learningat Eight grade in Sijunjung 20 middle school. This type of research is an experiment. The population of this research was Eighth grade students of Sijunjung Middle School 20. The technique of sampling was done randomly, namely VIIIA as the experimental class and VIIIB class as the control class. The instrument used was the final test with the reliability of the test r11=0.928. The results of the final test analysis, namely the two classes of samples were normal and homogeneous. The data analysis technique used the one-party t-test with t-count = 0.767 and t-table = 1.678, then the hypothesis is rejected. It was concluded that the mathematics learning outcomes of students by applying the Numbered Heads Together (NHT) type of cooperative learning model were not better than students mathematics learning outcomes by applying conventional learning in class VIII of Sijunjung Middle School 20.